Cavectomy following thrombectomy for Wilms’ Tumour with intracaval tumour thrombus: a case report and literature review - Sufian Chan, Aiman Adi; Salleh, Muhammad Azri; Nazmi, Muhammad Luqman; Ab. Rahman, Norhafiza; Othman, Mohd Yusran; Zahari, Zakaria (2022)
Introduction: Wilms’t tumour is the commonest renal tumour in children. With a predisposition of forming tumour thrombus in blood vessels, tumour extension into renal veins and inferior vena cava (IVC) has been reported in up to 10% of cases. Neoadjuvant chemotherapy has been shown to promote intracaval tumour regression, however in cases of persistent thrombus, thrombectomy is required along with the radical nephrectomy via cavotomy. We shared a rare complication of thrombectomy which required a cavectomy.